THE SOCIAL CAPITAL IN COMMUNITY PREPAREDNESS TOWARDS THE LANDSLIDE DISASTER IN PAGERHARJO KULONPROGO - Dina Ruslanjari; Titis Puspita Dewi (Jurnal Kawistara, 2018)
This study examines the social capital in case of people preparedness towards landslide. This research was conducted at Pagerharjo Village, Kulonprogo District where the location is categorized as the landslide prone area. The aim of this study is to find out the social capital for people preparedness in executing the landslide mitigation at Pagerharjo Village, Menoreh Mountains, Kulonprogo District. The research used qualitative descriptive method, with 9 out of 20 hamlets were selected as samples by purposive sampling. The sampling was taken in the location that has the landslide prone to the high landslide prone. People in Pagerharjo especially in the 9 hamlets have understood that their village is medium-to-highly vulnerable areas, especially in rainy season. The theory used in this study is Coleman’s social capital. The result of this research proves that the Pagerharjo people have social capital in disaster mitigation. The mitigation can be practiced as disaster socialization, mutual cooperation, structural mitigation, cultural, and leadership aspect. The community has also local belief from their ancestors which is the mixture of religion and culture in case of landslide mitigation. The willingness to transmigrate is the form of social capital dimension obtained from a sense of togetherness and trust in leaders at the levels of hamlet, village, and the local government.